Effect of manual osteopathic techniques on the autonomic nervous system, respiratory system function and head-cervical-shoulder complex—a systematic review - Stępnik, Jakub; Czaprowski, Dariusz; Kędra, Agnieszka (Frontiers in Medicine, 2024)
Background. Osteopathic manual techniques are now widely used in medicine worldwide. At present, there are no clear conclusions regarding the possibility of affecting the function of the autonomic nervous system (ANS), respiratory system and head-cervical-shoulder complex by manual osteopathic techniques. Objectives. The aim of the study was to review the current literature regarding the possible impact of osteopathic manual techniques on the state of the autonomic nervous system, spirometric parameters of the respiratory system and the state of the head-collar-shoulder complex. Methods. Publications have been searched in the following databases: PubMed, Virtual Health Library and Cochrane Central Register of Controlled Trials. The search strategy included keywords related to manual osteopathic treatment, autonomic nervous system, spirometry, respiratory function and head, neck and shoulder pain. The methodological quality of the included studies was assessed. The PRISMA guidelines were used for the systematic review. Studies from 2010 -2023 were selected. Results. Using the proposed descriptions and manual searches from the literature of other works, 40 studies were found, out of which 22 were rejected because they did not meet the inclusion criteria. The analysis included: 15 randomised controlled trials, 3 pilot studies.Studies clearly show the effect of OMT on both spirometric parameters and the condition of the head-collar-shoulder complex. Most often this translates into improved ANS performance, but there are exceptions.